Pengembangan Aplikasi Augmented Reality Untuk Pendidikan Komponen Transmisi Manual Mobil Pada Platform Android - Rofik Hakiki; Anita Fira Waluyo (Progresif: Jurnal Ilmiah Komputer, 2024)
Education is a fundamental need that plays a crucial role in determining the future progress of a nation and improving the quality of human resources. Practical learning in the automotive field, such as Light Vehicle Engineering (TKR), requires practical tools, especially car and motorbike components. The limited amount of equipment causes the practicum to be less efficient because each student must queue, resulting in a lack of student interest and enthusiasm for learning. Using technology as a learning medium can increase students' interest in learning, one of which is introducing car manual transmission components. This research aims to develop an interactive and innovative learning application for introducing car manual transmission components so that students can easily recognize manual transmission components and their functions. The methodology applied uses ADDIE, which consists of analysis, design, development, implementation, and evaluation. The present study successfully demonstrates the interactive display of three-dimensional manual transmission components within the context of an automobile. The results of various tests conducted using a black box corroborate the full functionality of all features associated with the system.Keywords: Learning Media; Augmented Reality; Marker Based; Vuforia; Manual Transmission   AbstrakPendidikan berperan dalam menentukan arah kemajuan masa depan bangsa, selain itu pendidikan dianggap sebagai kebutuhan pokok yang krusial dalam meningkatnya kualitas sumber daya manusia. Pembelajaran praktikum di bidang otomotif, seperti Teknik Kendaraan Ringan (TKR) memerlukan beberapa alat praktikum, terutama seperti komponen mobil dan motor. Keterbatasan jumlah peralatan menyebabkan praktikum menjadi kurang efisien karena siswa harus antri, mengakibatkan kurangnya minat belajar siswa. Diharapkan penggunaan teknologi media pembelajaran dapat meningkatkan antusiasme siswa dalam mengikuti pelajaran, salah satunya dalam pengenalan komponen transmisi manual mobil. Penelitian ini bertujuan untuk mengembangkan aplikasi pembelajaran pengenalan komponen transmisi manual mobil yang interaktif dan inovatif, agar siswa dapat dengan mudah mengenali komponen transmisi manual berikut dengan fungsinya. Metodologi yang diterapkan menggunakan ADDIE, langkahnya terdiri dari Analysis, Design, Development, Implementation, dan Evaluation. Penelitian ini berhasil menampilkan objek 3 dimensi berupa komponnen transmisi manual pada mobil yang interaktif, serta hasil pengujian dengan blackbox menunjukan semua fitur dapat bekerja dengan baik.Kata kunci: Media Pembelajaran; Augmented Reality; Marker Based; Vuforia; Transmisi manual